Perbandingan Efisiensi Biaya Bank Umum Syariah di Indonesia Sebelum dan Sesudah Spin-Off (Dengan Pendekatan Parametrik) - Rafika Rahmawati (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2016)
In this study conducted a comparative analysis of the level of efficiency in the commercial bank of sharia before and after the spin-off, expected the sharia can getan idea of things that need to be improved so that factors inefficiencies can be minimized and encouraged to immediately change the form of its businesses intosharia bank. The measurement of efficiency using parametric approach Stochastic Frontier Approach (SFA) and the comparison of the level of efficiency before andafter the spin-off using hypothesis testing using a paired t test (paired t-test). Where the bank is the object of research, BJB Sharia. The results showed that the averagelevel of cost efficiency in BJB Islamic Banks prior to the spin-off in the amount of 99.92% and after the spin-off amounted to 99.97%. There is significant/significant between BJB Islamic Banks (BJB Sharia) before and after the spin-off. BJB Sharia after the spin-off is more efficient in managing their funds than when prior to the spin-off.